The summer of chasing mermaids - Ockler, Sarah (Simon Pulse, 2015)
After a boating accident takes her beautiful singing and speaking voice from her, Elyse d'Abreau, the youngest of six sisters, leaves her home in Tobago to stay in an Oregon seaside town where Christian Kane, a notorious playboy, challenges her to express herself and to overcome her fear of the sea.